Job satisfaction and employee performance of SMEs in Cameroon - FOKAM , Jeff Astein MBAH; NGOATA , Sylvanus Diangha; MAFEU , Pousseu Darius TABET (Revue Internationale des Sciences de Gestion, 2022)
Small and medium businesses are critical to a country's economic success (Ariyo, 2005). They are critical to the economies of developing countries like Cameroon, where obstacles such as poverty eradication, corruption, and unemployment are still big concerns for inhabitants, leading to a very high death rate of small and Medium size enterprises. The objective of this research is to analyse the impact of job satisfaction on the performance of employees in Small and Medium Size enterprises in Cameroon. To realise this objective, Primary data was collected using a non-probabilistic sampling technic through a structured questionnaire administered on 50 respondents from selected SMEs in the center Region of Cameroon. The data was analysed using the Pearson correlation coefficient and the ordinary Least Square regression. The results show a positive and significant relationship between job satisfaction (captured using compensation and working environment) and employee performance of SMEs in Cameroon, these results corroborates those of (Alamdar et al.,2012). And from these results, we propose that SMEs in Cameroon should adopt compensation policies based on equity and not equality With respect to the working environment, SMEs should adopt appropriate ergonomically policies so that the health and safety of their workers should be ensured thereby satisfying them physically and psychologically.